2014
DOI: 10.1177/2047487314525531
|View full text |Cite
|
Sign up to set email alerts
|

What proportion of symptomatic side effects in patients taking statins are genuinely caused by the drug? Systematic review of randomized placebo-controlled trials to aid individual patient choice

Abstract: Only a small minority of symptoms reported on statins are genuinely due to the statins: almost all would occur just as frequently on placebo. Only development of new-onset diabetes mellitus was significantly higher on statins than placebo; nevertheless only 1 in 5 of new cases were actually caused by statins. Higher statin doses produce a detectable effect, but even still the proportion attributable to statins is variable: for asymptomatic liver enzyme elevation, the majority are attributable to the higher dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(145 citation statements)
references
References 37 publications
4
129
0
12
Order By: Relevance
“…However, they are not supported by the randomized controlled trial evidence: in particular, statin therapy has been found to be no less well tolerated than placebo (see below and webtable). 52,62,[236][237][238][239] As is discussed above, the potential biases inherent in studies without both randomly assigned control groups and blinded ascertainment of outcomes limit their ability to demonstrate causal associations (except for large effects on rare outcomes). This is particularly the case for symptomatic adverse events that are attributed to statin use, especially if such reports have been prompted by guidance from clinicians to their patients or from patient information leaflets and other sources.…”
Section: Other Adverse Events That Have Been Attributed To Statin Thementioning
confidence: 99%
See 1 more Smart Citation
“…However, they are not supported by the randomized controlled trial evidence: in particular, statin therapy has been found to be no less well tolerated than placebo (see below and webtable). 52,62,[236][237][238][239] As is discussed above, the potential biases inherent in studies without both randomly assigned control groups and blinded ascertainment of outcomes limit their ability to demonstrate causal associations (except for large effects on rare outcomes). This is particularly the case for symptomatic adverse events that are attributed to statin use, especially if such reports have been prompted by guidance from clinicians to their patients or from patient information leaflets and other sources.…”
Section: Other Adverse Events That Have Been Attributed To Statin Thementioning
confidence: 99%
“…For example, there was no excess of discontinuations related to adverse events with statin therapy, and any excesses of muscle-related symptoms due to statin therapy occur in only about 0.1-0.2% of patients during each year of treatment. 52,150,236,237,243 …”
Section: Proven Harms Of Statin Therapy But Minimal Symptomatic Sidementioning
confidence: 99%
“…В ряде исследований (TNT, SAGE, PROVE-IT TIMI 22) применение высокой дозы статинов ассоциировалось с более высокой частотой повышения показателей функциональных печеночных тестов у по-жилых по сравнению с более молодыми людьми [24][25][26], а отмена статинов вследствие бессимптомного по-вышения печеночных трансаминаз, согласно результатам мета-анализа 14 РКИ по первичной профилактике ССЗ (n=46262), наблюдалась на 0,4% чаще у пожи-лых, чем у более молодых лиц [27].…”
Section: влияние гиперлипидемии на заболеваемость и смертность пожилыunclassified
“…По-вышение АР их возникновения по данным мета-анализа 14 исследований по первичной профилактике соста-вило 0,5% [95% доверительный интервал (ДИ) 0,1-1%; p=0,012], однако исходы у пациентов с впервые за-регистрированным повышением уровня HbA1c в ходе РКИ не отличались от таковых у пациентов без диабе-та [27].…”
Section: влияние гиперлипидемии на заболеваемость и смертность пожилыunclassified
“…À la lumière des résultats de l'enquête canadienne sur les mesures de santé de 2012-2013, une dyslipidémie a été mesurée, ou autodéclarée, chez 38 % des répondants âgés de 18 à 79 ans. Parmi les personnes dyslipidémiques, 51 % étaient au fait de leur état de santé et 30 % de ces derniers contrôlaient leur taux de cholestérol sanguin au moyen de médicaments (Statis-au traitement [7][8][9][10][11]. L'étude PRIMO (prédiction du risque musculaire en observationnel) rapportait, chez les utilisateurs de statines, une incidence de 11 % de dysfonctions musculaires, tous symptômes confondus, dont 4 % avec symptômes suffisamment handicapants pour limiter les activités de la vie quotidienne (AVQ) et 0,4 % nécessitant un alitement complet [12].…”
Section: Les Statines : Usage Et Sécuritéunclassified